La gestión pública y su incidencia en la seguridad ciudadana en la unidad educativa “Carlos julio Arosemena tola”, Quevedo 2023. - Calderón Palma, Johanna Del Rocío (2025)
This research highlights citizen security that has gained importance in recent decades due to the increase in violence and crime, which has driven a change in public policies towards a more citizen-centered approach. In Ecuador, this approach is crucial in the educational field, where protecting students and staff is essential for community development. Therefore, this work needs to evaluate the impact of public management on the security of the “Carlos Julio Arosemena Tola” Educational Unit. The methodology used includes surveys and interviews aimed at teachers, parents and educational authorities, as well as direct observations to capture perceptions about safety in the school environment. The results indicate a generalized perception of insecurity and little knowledge about current policies. In addition, deficiencies have been identified in the coordination between local and educational authorities. In conclusion, it is essential to strengthen public management in the school environment through greater community participation and adequate allocation of resources. This will create a safer educational environment that is conducive to learning, benefiting the entire educational community.